In vitro killing of Schistosomula of Schistosoma japonicum by Monoclear Phagocytes from normal humans, rats and mice - Acosta, Luz Pablo (1983)
In the present investigation, we compared the degree of susceptibility to Schistosome japonica infection of mice (BALB/c) and outbred rats by a primary infection of cercariae and subsequent recovery of adult worms. We also compared the contributions of monocular phagocytes, specifically monocytes from humans and macrophages from mice and rats, to innate resistance using an in vitro system. Mice and rats infected with cercariae (40 each) of S. japonica were sacrificed at 4 weeks and adult worms were recovered. by perfusion of the mesenteric vasculature, mice had a mean percent recovery +/- S.E.M. of 71.62 +/- 1.47 of mature worms from infecting cercariae whereas rats had only 33.00+/- 1.67. Adherent monolayers prepared from human peripheral blood mononucclear cells induced significant schistosomula killing as detected by methylene blue dye uptake. At 24 hours of incubation, monocytes killed a mean percent of 7.9 +/- 0.45 of the incubated schistosomula. The mean percent dead schistosomulation in culture medium alone was only 0.07 the difference between these two observed values was significant at the 5% level using student's t-test. Monolayers obtain from pooled peritoneal exudate cells of normal mice also killed a significant percentage of schistosomula (9.13 +/- 1.2). however, the difference between killing by mice macrophages and human monocytes (mice macrophages vs. human monocytes) was not significant. Macrophages from individual outbred rats killed relatively high percentage of incubated schistosomula (13.94 +/- 1.3). When compared with the rest of the experimental groups, the mean percent killing by rat macrophages was highly significant at the 5% level (student's t-test) as follows: vs. human monocytes, vs. mice macrophages and vs. co0ntrol media.
Keywords: Rats -- Infections; Schistosoma japonicum -- Infections